Differential Accumulation of Aroma Compounds in Normal Green and Albino-Induced Yellow Tea (Camellia sinensis) Leaves - Dong, Fang (Molecules, 2018)
Tea (Camellia sinensis) cultivars with green leaves are the most widely used for making tea. Recently, tea mutants with white or yellow young shoots have attracted increasing interest as raw materials for making “high-quality” tea products. Albino teas are generallycharacterized as having metabolites of relatively high amino acid content and lower catechin content. However, little is known about aroma compounds in albino tea leaves. Herein, we compared original normal leaves (green) and light-sensitive albino leaves (yellow) of cv. Yinghong No. 9. GC-MS was employed to analyze endogenous tea aroma compounds and related precursors. Quantitative real time PCR was used to measure expression levels of genes involved in biosyntheses of tea aromas.The total contents of most endogenous free tea aromas, including aroma fatty acid derivatives, aroma terpenes, and aroma phenylpropanoids/benzenoids, and their glycosidically bound aroma compounds, were lower in yellow leaves than in green leaves. The content of the key precursor geranyl diphosphate (GDP) and expression levels of key synthetic genes involved in the formation of linalool, a major aroma compound in cv. Yinghong No. 9, were investigated. Linalool content was lower in albino-induced yellow leaves, which was due to the lower GDP content compared with normal green leaves.